English Language Teaching Issues Encountered By English Teachers In Rural Settings Of East Lombok: Masalah Pengajaran Bahasa Inggris Yang Dihadapi Oleh Guru Bahasa Inggris Di Pedesaan Lombok Timur - Budi Setiawan; Riza Nadia (INGGARA (Jurnal Pendidikan Bahasa Inggris dan Bahasa Arab), 2022)
The purpose of this research is to investigate the framework of questions concerning the challenges faced by English instructors in remote areas of East Lombok. In this study, a qualitative approach was used. This research was carried out in East Lombok, using purposive sampling. This survey's participants are six teachers from Sambelia, Sembalun and Wanasaba sub-district schools, specifically the educators at SMPN 2 Sambelia, SMP Islam Darul Ilmi Otorita, MAS Maraqitta'limat Al-Hamzar Belanting, MTS Maraqitta'limat Sembalun Bumbung, SMKS Maraqitta'limat Sembalun and SMK Sa'adatul Islamiah NWDI. This research used an interview technique that included a phone recording. The audio recorded interview questions were transcribed verbatim for proper analysis and interpretation. The findings of this study revealed that some rural teachers discovered some hindrances in teaching English such as limited infrastructure, time constraint,  lack of parental involvement, students’ low motivation, and less English application. It is uncovered that the education in rural schools of East Lombok remains unsatisfactory due to numerous barriers in the teaching and learning process.